Along with intraspecific functional trait variation, individual performance is key to resolving community assembly processes. (30th August 2020) - Doudová, Jana; Douda, Jan
Abstract: Species contributing high proportions to community biomass strongly influence ecosystem processes within the community. Studies have shown that dominant species may serve as nurse plants, helping to ensure biomass stability of the subordinate species under stress conditions. The question is widely debated as to whether either niche differentiation or neutral processes drive the net outcome of plant interactions within a subordinate plant community. To answer this question, requires precise estimates of individual variation in functional traits and performance. In a 5‐year mesocosm experiment, the functional responses of a subordinate plant community to the removal of the dominant species were evaluated across two drought‐stress scenarios. Small‐scale (i.e. large pots) wetland communities were constructed comprising one dominant species Carex elata and three subordinate species. Removal of the dominant species allowed evaluation of the net effects of drought and interspecific interactions. We estimated the functional divergences for three traits (SLA, leaf dry matter content and allocation to height growth) and compared these with performance differences quantified individually. This enabled distinctions to be made between deterministic (i.e. niche differentiation) and neutral processes driving the drought response of the subordinate community. We showed that the dominant species decreased relative performance differences within the subordinate plant community under conditions of permanent drought stress. These changes were associated with the convergence of traits related to resource acquisition and growth. The dominant species equalized species performance differences by supressing relatively drought‐tolerant species with low competitive ability and by supporting the less drought‐tolerant species with relatively high competitive ability. Meanwhile, under conditions of inter‐annual drought, the subordinate species likely coexisted due to differentiation in resource‐use strategies and the interaction with the dominant species. Inclusion of individual variation in performance with a functional trait approach provides valuable insights into the processes structuring plant communities. Ours is the first study to provide evidence that subordinate species exposed to drought may coexist via neutral processes arising from their interactions with the dominant species, leading to functional convergence of traits associated with the trade‐off between stress tolerance and competitive ability. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.